2004
DOI: 10.1002/eji.200424886
|View full text |Cite
|
Sign up to set email alerts
|

Homophilic interaction of NTBA, a member of the CD2 molecular family: induction of cytotoxicity and cytokine release in human NK cells

Abstract: NK-T-B antigen (NTBA) is a CD2 family member that functions as a coreceptor in human NK cell activation. Several receptor/ligand interactions occur between different members of this molecular family. In this study, in order to identify the natural ligand of NTBA, we produced a chimeric protein formed by the NTBA extracellular region fused with the Fc portion of human IgG1 (termed NTBA-Fc*). NTBA-Fc* specifically binds to NTBA cell transfectants but not to cells transfected with other CD2 family members includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 35 publications
1
75
0
Order By: Relevance
“…These Ly108-positive NK cells were lost when cells were propagated and activated in vitro with IL-2. The absence of Ly108 on most mouse NK cells was surprising given that human NK cells uniformly express high levels of NTB-A, the human Ly108 equivalent (11)(12)(13)(14). Ly108 was present on all liver NK-T cells, in keeping with a recent report (27) (Fig.…”
Section: Mouse Ly108 Is Expressed On T Cells and B Cells But Not Onsupporting
confidence: 85%
See 1 more Smart Citation
“…These Ly108-positive NK cells were lost when cells were propagated and activated in vitro with IL-2. The absence of Ly108 on most mouse NK cells was surprising given that human NK cells uniformly express high levels of NTB-A, the human Ly108 equivalent (11)(12)(13)(14). Ly108 was present on all liver NK-T cells, in keeping with a recent report (27) (Fig.…”
Section: Mouse Ly108 Is Expressed On T Cells and B Cells But Not Onsupporting
confidence: 85%
“…Early studies showed that engagement of Ly108 was able to promote SAPdependent natural cytotoxicity by human NK cells (11)(12)(13)(14). Subsequently, it was shown that stimulation of human CD4 ϩ T cells by an anti-Ly108 monoclonal antibody (mAb) enhanced T helper 1 (T H 1) cytokine release (15).…”
mentioning
confidence: 99%
“…These cDNAs were cloned from either existing MGC clones or amplified from mixed-tissue human cDNA essentially as described (Collins et al 2004). Within this set of proteins are published negative interactions (Martin et al 2001;Kumaresan et al 2002;Falco et al 2004;Flaig et al 2004;Romero et al 2005), outlined with black circles in Figure 1D.…”
Section: Avexis Validationmentioning
confidence: 99%
“…NTB-A, another member of the SRR family, is homophilic [30,31]. The presence of NTB-A on Baf3 cells effectively induces NTB-A-mediated NK cell cytotoxicity [27,32].…”
Section: Activation-induced Down-modulation Of 2b4 Surface Expressionmentioning
confidence: 99%